The Palgrave Handbook of Indian Migrants to South East Asia
XVIII, 591 p. 54 illus., 41 illus. in color.
Keywords: This Handbook is a charting exercise to determine contemporary patterns of Indian migration to Southeast Asia. It will determine two waves/sectors of the Indian migration process to Southeast Asia, high skilled migration and semi-skilled to low skilled migration. However, such a research project is not complete without understanding the context of social and political dilemmas of Indian communities in Southeast Asia as well as the interstitial spaces some Indian migrants or migrant communities might fall through as stateless Indians or Indian communities. The Handbook is premised largely on Indian-ASEAN, twenty-five years of partnering relations in diplomacy, politics, economy, people to people exchange, human capital development and exchange as well as coordinated infrastructural development. It reinforces the much-discussed ‘Look East’ and current ‘Act East’ initiatives of the Indian government, highlighting cooperation with the Southeast Asian and East Asian economies, as some political perspectives suggest, to counterbalance China’s economic influence in the region. S. Irudaya Rajan is Chair of the International Institute of Migration and Development, Kerala, India. Prior to this, he was a Professor at the Centre for Development Studies. Prof. Rajan is the Founder Editor in Chief of Migration and Development (Sage) and the editor of two Routledge series - India Migration Report and South Asia Migration Report. He has coordinated nine large-scale migration surveys in Kerala since 1998 (with K.C. Zachariah) and replicated the Kerala model of migration surveys in other states, including Goa (2008), Punjab (2009), Tamil Nadu (2015), and Odisha (2023) and has been instrumental in similar surveys in Gujarat (2011), and Jharkhand (2023).